1983
DOI: 10.1007/bf00914248
|View full text |Cite
|
Sign up to set email alerts
|

Child and parent evaluations of depression and aggression in psychiatric inpatient children

Abstract: This investigation examined the agreement between children and their parents on measures of depression and aggression. A total of 120 inpatient children (ages 7-13) and their mothers and fathers independently completed self-report and interview measures that focused on the children's dysfunction. Children and their parents differed in their ratings of each symptom area, with children providing significantly less severe ratings than their parents. Children who met DSM III criteria for major depression or conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
70
3

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(87 citation statements)
references
References 14 publications
14
70
3
Order By: Relevance
“…When the cutoff point of 13 was taken as threshold, the prevalence rate was somewhat higher (14.96%) than the prevalence figures of self-reported depressive morbidity obtained from studies in general population, but still much lower than those obtained from studies using the cutoff point of 13 of the CDI [17,43]. Since previous studies [10,24,27,48] indicate that CDI can be better used as a continuous measure of depressive symptoms [10] rather than as an accurate discriminatory (through cutoff scores) instrument for depression, further research using CDI along with other validated diagnostic measures for psychopathology in both clinical and nonclinical Greek populations (questionnaires and/or structured interviews) is needed. The particular cultural influences on children's depressive symptom reporting is an issue that should be further explored in future research in order to investigate whether lower mean cores in CDI (compared to studies in non-Greek populations) reflect lower rates of depressive symptoms, differences in the perception of the CDI items, or even cultural differences in the expression of depressive symptomatology.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…When the cutoff point of 13 was taken as threshold, the prevalence rate was somewhat higher (14.96%) than the prevalence figures of self-reported depressive morbidity obtained from studies in general population, but still much lower than those obtained from studies using the cutoff point of 13 of the CDI [17,43]. Since previous studies [10,24,27,48] indicate that CDI can be better used as a continuous measure of depressive symptoms [10] rather than as an accurate discriminatory (through cutoff scores) instrument for depression, further research using CDI along with other validated diagnostic measures for psychopathology in both clinical and nonclinical Greek populations (questionnaires and/or structured interviews) is needed. The particular cultural influences on children's depressive symptom reporting is an issue that should be further explored in future research in order to investigate whether lower mean cores in CDI (compared to studies in non-Greek populations) reflect lower rates of depressive symptoms, differences in the perception of the CDI items, or even cultural differences in the expression of depressive symptomatology.…”
Section: Discussionmentioning
confidence: 71%
“…The cutoff score of 19, corresponding to the 90th percentile, has been considered suitable for screening in the general population, while the cutoff score of 13, corresponding to the 65th percentile, has been suggested as being adequate for screening purposes in clinical samples [52]. However, with regard to clinical samples, there is a substantial body of research indicating that CDI cutoff scores cannot accurately distinguish between depressed and non-depressed individuals [10,24,27,48]. It has been shown that in clinical samples, CDI can be used as a preliminary continuous measure of depressive symptoms rather than a single evaluation instrument for a diagnosis of depression [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hopelessness (a ¼ .65e.80) was created from a series of variables originally used by Kazdin et al [34]. The scale measures the respondents' attitude and outlook regarding future prospects.…”
Section: Methodsmentioning
confidence: 99%
“…Kovacs (1992) reported adequate internal consistency and retest reliability for the scale. Evidence for the validity of this measure is well documented (e.g., Kovacs, 1992;Saylor, Finch, Spirito, & Bennett, 1984;Kazdin, Esveldt-Dawson, Unis, & Rancurello, 1983). Internal consistency of the CDI for this sample was .85; retest reliability was .70.…”
Section: Bias/prmentioning
confidence: 95%